Enhanced planar perovskite solar cell efficiency and stability using a perovskite/PCBM heterojunction formed in one step. Issue 6 (29th January 2018) - Zhou, Long; Chang, Jingjing; Liu, Ziye; Sun, Xu; Lin, Zhenhua; Chen, Dazheng; Zhang, Chunfu; Zhang, Jincheng; Hao, Yue
Abstract : Efficient perovskite/PCBM heterojunction is formed in one-step for perovskite solar cells with high performance and long-term stability. Abstract : Perovskite/PCBM heterojunctions are efficient for fabricating perovskite solar cells with high performance and long-term stability. In this study, an efficient perovskite/PCBM heterojunction was formed via conventional sequential deposition and one-step formation processes. Compared with conventional deposition, the one-step process was more facile, and produced a perovskite thin film of substantially improved quality due to fullerene passivation. Moreover, the resulting perovskite/PCBM heterojunction exhibited more efficient carrier transfer and extraction, and reduced carrier recombination. The perovskite solar cell device based on one-step perovskite/PCBM heterojunction formation exhibited a higher maximum PCE of 17.8% compared with that from the conventional method (13.7%). The device also showed exceptional stability, retaining 83% of initial PCE after 60 days of storage under ambient conditions.